2018
DOI: 10.1109/twc.2018.2802937
|View full text |Cite
|
Sign up to set email alerts
|

Link Selection in Hybrid RF/VLC Systems Under Statistical Queueing Constraints

Abstract: The co-deployment of radio frequency (RF) and visible light communications (VLC) technologies has been investigated in indoor environments to enhance network performances and to address specific quality-of-service (QoS) constraints. In this paper, we explore the benefits of employing both technologies when the QoS requirements are imposed as limits on the buffer overflow and delay violation probabilities, which are important metrics in designing low latency wireless networks. Particularly, we consider a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…We set γ s = 0.3 and β s = 0.7 and we consider different transmission power values. For each value of the transmission power, we find the value of θ that minimizes the channel-related buffer overflow probability, following (13). We then compute the average transmission rate that corresponds to the optimal channel log-moment generating function at that θ level, i.e., p o,c ρ .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We set γ s = 0.3 and β s = 0.7 and we consider different transmission power values. For each value of the transmission power, we find the value of θ that minimizes the channel-related buffer overflow probability, following (13). We then compute the average transmission rate that corresponds to the optimal channel log-moment generating function at that θ level, i.e., p o,c ρ .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…By imposing the QoS constraints based on the data link metrics, i.e. the limits on the buffer overflow and buffering delay probabilities, Hammouda et al [105] showed that the VLC links offered queuing delays lower than RF links when the data arrival rates at the transmitter buffer were low; however, the RF links supported the higher data arrival rates.…”
Section: A Optimizing Hybrid Vlc/rf Networkmentioning
confidence: 99%
“…With the availability of multiple RATs in B5G networks, suitable access device selection to improve provided QoS is possible. Although network-based approaches [15]- [21] provide a more optimal access device allocation, using such approaches would result in a huge amount of signaling information being transmitted between network elements and IoT nodes. Besides, scalability issues of network-core would arise because of the expected massive number of IoT devices.…”
Section: Background and Related Work A Motivation And Problem Stmentioning
confidence: 99%
“…The paper discusses using indoor networks and transportation systems' while considering a Femto AP and a LiFi AP. A hybrid WiFi and LiFi system for QoS provisioning using link selection is proposed with buffer overflow constraints and delay in [21]. Because of the smaller coverage regions of LiFi APs, a concept of handover skipping is proposed in [39] to enable handover between nonadjacent APs for hybrid WiFi and LiFi networks.…”
Section: B Related Workmentioning
confidence: 99%